The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.srhc.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the midwifery profession in Nepal – Uncovering actors' connections using a Complex Adaptive Systems framework

Abstract: Objectives: To explore how actors connect in a system aiming at promoting the establishment of a midwifery profession in Nepal.Methods: A qualitative explorative study based on the framework of Complex Adaptive Systems. Semi-structured interviews were conducted with 17 key people representing eight different organisations [actors] promoting the development of the midwifery profession. Results:The actors' connections can be described with a complex set of facilitators for and barriers to promoting the establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The test showed that none of the loss in performance score was statistically significant b For skilled birth attendants only mentors further trained and mentored by provincial mentors, as successfully implemented in Uganda in the area of MNC [26]. Nepal has, however, taken a very promising step forward by launching a midwifery education program [27][28][29]. It is expected that the soon-to be deployed midwives will help improve the clinical skills of ANMs and nurses.…”
Section: Sustainabilitymentioning
confidence: 99%
“…The test showed that none of the loss in performance score was statistically significant b For skilled birth attendants only mentors further trained and mentored by provincial mentors, as successfully implemented in Uganda in the area of MNC [26]. Nepal has, however, taken a very promising step forward by launching a midwifery education program [27][28][29]. It is expected that the soon-to be deployed midwives will help improve the clinical skills of ANMs and nurses.…”
Section: Sustainabilitymentioning
confidence: 99%
“…consumer and religious groups), researchers, professional and international associations, and donor agencies • Policies are influenced by interests that have concentrated benefits and diffuse costs • Interest groups play a role in supporting or opposing the integration of midwifery in the health system • In LMICs, bilateral and multilateral donors work alongside local governments • In HICs, professional associations play a strong role in political lobbying • Interests are closely related to institutions (policy networks) as well as ideas as interest groups often reflect and/or can influence societal values • Interest groups play an important role in advancing midwifery in the health system by (1) creating partnerships to improve SRHR [ 45 , 67 ]; (2) promoting regulation and accreditation (e.g. accreditation requirements, setting standards, policies and guidelines) [ 63 , 68 – 70 ]; (3) capacity-building, including midwifery research [ 71 , 72 ]; (4) policy leadership and decision-making [ 43 ]; and (5) lobbying governments/advocacy [ 73 , 74 ] • Strong physician and hospital interest groups created a monopoly over maternity care (United States, Canada, Australia, and Mexico) [ 37 , 38 , 51 , 55 , 75 – 77 ] and impede midwives from practicing to their full scope [ 78 , 79 ] • Tensions within the profession between nurse midwives and midwives (United States) [ 80 ] • Marginalisation of midwifery through dominant stakeholder groups [ 50 ] • Competing interests from nursing organisations created interprofessional tensions (Nepal) and limited establishing midwifery as an independent profession [ 81 ] • Barriers existed in accessing evidence published by African midwives (e.g. African nursing and midwifery research is often published in non-indexed journals) [ 72 ] • Creation of interest groups to participate in the policy-making process [ 4 ] and strengthening existing groups in order to participate in the decision-making process (Nepal) [ 81 , 82 ] • Consultations with interest groups to create culturally safe midwifery care (Canada) [ 34 , 56 – ...…”
Section: Resultsmentioning
confidence: 99%
“…accreditation requirements, setting standards, policies and guidelines) [ 63 , 68 – 70 ]; (3) capacity-building, including midwifery research [ 71 , 72 ]; (4) policy leadership and decision-making [ 43 ]; and (5) lobbying governments/advocacy [ 73 , 74 ] • Strong physician and hospital interest groups created a monopoly over maternity care (United States, Canada, Australia, and Mexico) [ 37 , 38 , 51 , 55 , 75 – 77 ] and impede midwives from practicing to their full scope [ 78 , 79 ] • Tensions within the profession between nurse midwives and midwives (United States) [ 80 ] • Marginalisation of midwifery through dominant stakeholder groups [ 50 ] • Competing interests from nursing organisations created interprofessional tensions (Nepal) and limited establishing midwifery as an independent profession [ 81 ] • Barriers existed in accessing evidence published by African midwives (e.g. African nursing and midwifery research is often published in non-indexed journals) [ 72 ] • Creation of interest groups to participate in the policy-making process [ 4 ] and strengthening existing groups in order to participate in the decision-making process (Nepal) [ 81 , 82 ] • Consultations with interest groups to create culturally safe midwifery care (Canada) [ 34 , 56 – 58 ] • Professional interest groups came together to strengthen health systems through (1) awareness campaigns; (2) lobbying (agenda-setting); and (3) training, advocacy and coalitions of interested stakeholders to inform education and policy [ 11 , 66 – 68 , 83 ] • Midwifery organisations used counter social movements to influence public opinion [ 49 ] • Researchers advocated for evidence-informed policies on midwifery [ 47 ] • Collaborative networks of health professional groups raised awareness of rising caesarean rates (Latin America) [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One key barrier to improving mental health care in primary-care settings is the low numbers of skilled health workers who are trained in providing (maternal) mental health care (Saraceno et al, 2007). In Nepal, there is the added problem that the profession of midwifery is in its infancy (Bogren et al, 2013;Bogren et al, 2016). A needs assessment of mental health training for Auxiliary Nurse Midwives (ANMs) in Nepal, showed a lack of training on mental health issues related to pregnancy and childbirth (Simkhada et al, 2016).…”
Section: Introductionmentioning
confidence: 99%